2017
DOI: 10.1016/j.neulet.2016.12.063
|View full text |Cite
|
Sign up to set email alerts
|

Cellular permeation of large molecules mediated by TRPM8 channels

Abstract: While most membrane channels are only capable of passing small ions, certain non-selective cation channels have been recently shown to have the capacity to permeate large cations. The mechanisms underlying large molecule permeation are unclear, but this property has been exploited pharmacologically to target molecules, such nerve conduction blockers, to specific subsets of pain-sensing neurons (nociceptors) expressing the heat-gated transient receptor potential (TRP) channel TRPV1. However, it is not clear if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 50 publications
(94 reference statements)
0
14
0
Order By: Relevance
“…Moreover, cold hypersensitivity associated with inflammatory and neuropathic injury is diminished in the absence of this channel 24 , 27 , 28 . Two reports suggested that TRPM8 does not permeate large cations in vitro and in vivo 29 , 30 , whereas we and others have recently shown uptake of large cations in both heterologous cells and sensory neurons expressing TRPM8 channels, as well as found that co-application of TRPM8 agonists with QX-314 blocked Na + currents in these cells 6 , 31 . Nonetheless, while these latter studies showed that TRPM8 channels permeate large cations, it was unclear if they can be employed for cell-specific targeting of molecules in vivo.…”
Section: Introductionmentioning
confidence: 50%
See 2 more Smart Citations
“…Moreover, cold hypersensitivity associated with inflammatory and neuropathic injury is diminished in the absence of this channel 24 , 27 , 28 . Two reports suggested that TRPM8 does not permeate large cations in vitro and in vivo 29 , 30 , whereas we and others have recently shown uptake of large cations in both heterologous cells and sensory neurons expressing TRPM8 channels, as well as found that co-application of TRPM8 agonists with QX-314 blocked Na + currents in these cells 6 , 31 . Nonetheless, while these latter studies showed that TRPM8 channels permeate large cations, it was unclear if they can be employed for cell-specific targeting of molecules in vivo.…”
Section: Introductionmentioning
confidence: 50%
“…As we find that large cations permeate TRPM8 channels expressed in heterologous and native cells, and that QX-314 blocks sodium currents in TRPM8-expressing cells stimulated with TRPM8 agonists 31 , we asked if TRPM8 activation in the presence of QX-314 can alter cold sensitivity in vivo. First, to confirm that in vivo thermal responses can be blocked in our hands using TRP channel activation, we examined heat responses in adult wild-type mice after injection of QX-314 and the TRPV1 agonist capsaicin 8 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anionics such as Lucifer Yellow (457 Da, 2 À ) Fluo-4 (736.63 Da, 4 À ), Fura-2 (832 Da, 5 À ), and fluorescein (332.31 Da, 1 À ) are usually ion markers or intracellular structures [27,59,60]. A study by McCoy et al [42] on the permeabilization of large molecules mediated by the TRPM8 receptor, the cationic dye PO-PRO-3 (605.30 Da, 2 + ), was used to measure the dilation of the pore. However, it is not common to use fluorophores other than those mentioned above, having a great scenario to be explored in ionic conductance tests.…”
Section: Fluorescent Dyes and Their Use In The Study Of Pores By Ion mentioning
confidence: 99%
“…Recent progress has been made in selective targeting of different subsets DRG neurons [42-47]. Local anesthetics are mostly uncharged molecules that penetrate the membrane of all neurons, blocking not only sensory neurons but also motor and autonomic neurons, generating undesired effects such as blood pressure changes and motor deficits.…”
Section: Targeting Drg Neurons By Selective Nerve Blockadementioning
confidence: 99%